The Impact of Work-family Conflict on Employees’ Turnover Intention in Chinese Internet Industry: The Mediating Role of Employee Well-being - Zhang, Yue-Meng (2022)
The Internet industry has grown rapidly in China in recent years. Subsequently, unlike other industries, the working hours and workload in China's Internet industry are greater and overtime is more common. Problems like work-family conflict, low well-being and high turnover rates are particularly problematic in the Chinese Internet industry. Accordingly, this study investigates the interrelationship among work-family conflict, employee well-being, and turnover intentions based on the conservation of resources (COR) theory. It used the questionnaire to survey employees in the Chinese Internet industry. A total of 333 valid questionnaires were collected. The findings indicate that there are significant effects between work-family conflict, employee well-being and turnover intentions, which is consistent with the results of previous studies. The higher the work-family conflict the lower the well-being of employees, while lower well-being can cause higher turnover intentions. Moreover, the findings suggest that employee well-being mediated the relationship between work-family conflict and turnover intention. Additionally, the study found the impact of age, marital status, number of children, age of the youngest child, and organisational tenure on work-family conflict.